Development of Polymeric Cargo for Delivery of Photosensitizer in Photodynamic Therapy - Byoung-chan Bae; Kun Na (International Journal of Photoenergy)
Photodynamic therapy (PDT), which employs photosensitizers (PSs), a light source with appropriate wavelength, and oxygen molecules, has potential for the treatment of various tumors and nononcological diseases due to its high efficiency in directly producing cellular death, vascular shutdown, and immune activation. After the clinical success of Photofrin (porphyrin derivative), many PSs were developed with improved optical and chemical properties. However, some weak points such as low solubility and nonspecific phototoxicity induced by hydrophobic PSs still remain. In order to overcome these problems, various polymeric carriers for PS delivery have been intensively developed. Here, we report recent approaches to the development of polymeric carriers for PS delivery and discuss the physiological advantages of using polymeric carriers in PDT. Therefore, this paper provides helpful information for the design of new PSs without the weaknesses of conventional ones.